2007
DOI: 10.4049/jimmunol.178.3.1783
|View full text |Cite
|
Sign up to set email alerts
|

CD59, a Complement Regulatory Protein, Controls Choroidal Neovascularization in a Mouse Model of Wet-Type Age-Related Macular Degeneration

Abstract: We have shown that membrane attack complex (MAC) formation via the activation of the alternative pathway plays a central role in the laser-induced choroidal neovascularization (CNV). This study was undertaken to understand the role of a complement regulatory protein, CD59, which controls MAC assembly and function, in this model. CNV was induced by laser photocoagulation in C57BL/6 and Cd59a−/− mice using an argon laser. Animals from each group were sacrificed on day 1, 3, 5, and 7 postlaser. Retinal pigment ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
78
1
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(87 citation statements)
references
References 56 publications
7
78
1
1
Order By: Relevance
“…Failure of C3-and C5-deficient mice to develop laser-induced CNV supports the hypothesis that C contributes to angiogenesis (12,13). Consistent with this, the degree of CNV is decreased in C3aR-and C5aR-deficient mice or in animals treated with C3aR and C5aR antagonists (11) or with recombinant CD59a-Fc, which prevents the assembly of MAC (14). However, Langer et al (15) have recently reported an inhibitory role of C on angiogenesis in a mouse model of retinopathy of prematurity.…”
Section: Complement | Vasculogenesis | Animal Modelssupporting
confidence: 75%
“…Failure of C3-and C5-deficient mice to develop laser-induced CNV supports the hypothesis that C contributes to angiogenesis (12,13). Consistent with this, the degree of CNV is decreased in C3aR-and C5aR-deficient mice or in animals treated with C3aR and C5aR antagonists (11) or with recombinant CD59a-Fc, which prevents the assembly of MAC (14). However, Langer et al (15) have recently reported an inhibitory role of C on angiogenesis in a mouse model of retinopathy of prematurity.…”
Section: Complement | Vasculogenesis | Animal Modelssupporting
confidence: 75%
“…Conversely, mice deficient in CD59 (cd59 −/− ), a negative regulator of complement, exhibit increased deposition of the C5a-9 MAC complex in CNV lesions, as well as more severe laser-induced CNV. Intraperitoneal or intravitreal administration of recombinant CD59 protein reverses this affect, leading to decreased MAC deposition, reduced expression of angiogenic factors, and dramatically decreased CNV development in the cd59 −/− mice (13% incidence of CNV versus 94% in controls) [53]. These data in murine models of laser-induced CNV support studies in human AMD that overactivity of the complement system, at least in part, mediates AMD pathogenesis, including CNV.…”
Section: Complement Components and Complement Regulatory Proteins In supporting
confidence: 59%
“…Evidence from both human and animal studies supports a key role for complement activation in the development of CNV (7)(8)(9)(10)(11). We demonstrated that membrane attack complex (MAC) formation via the alternative pathway activation is important for the release of angiogenic growth factors that are critical for the induction of CNV in mouse model (9).…”
mentioning
confidence: 79%
“…Laser-induced mouse model of CNV in which Bruch's membrane (BM) is disrupted by laser photocoagulation is well established and is used by an increasing number of investigators (4 -7). Over the last ten years, we have noted that rodent model of laser-induced CNV has provided valuable information and contributed significantly to our understanding of the underlying mechanisms involved in the pathogenesis of new vessel growth from the choroid (7)(8)(9)(10).…”
mentioning
confidence: 99%